Perancangan Program Sistem Pakar Berbasiskan Web untuk Rehabilitasi Medik Penderita Skoliosis - Santoso, Djunaidy; Megawati, Vita (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The application program created in this research is a web-based expert system program for medical rehabilitation of patients with scoliosis. The program aims to make consultation between users and the experts. With the expert system method based on components of medical science this application can help achieve thegoal, that is to make easier for people to recognize and prevent the occurrence of scoliosis, as well as to make easier for doctors making conclusions. Bu using this expert system, students can make decisions quickly when there are problems with Scoliosis disease.